1965
DOI: 10.3109/00016346509153994
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Obstetrical Phenomena1

Abstract: The seasonal variations in disease reflect a) the internal biological rhythm which originally developed to guarantee the preservation of the species (the rhythm is usually related to sunlight or temperature), b) secondary stress phenomena influenced by season (e.g. infections, different working conditions), c) seasonal phenomena caused by customs (festivals, variation in diet etc., based on tradition).The authors have earlier investigated the seasonal variation in the number of births and in cystic glandular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because of the accessibility of birthdates, we believe that the assessment of birthcurves of patients with all kinds of pathology is a very useful approach to elucidating the etiology and the delineation of congenital malformations and psychopathology. The same holds true for the epidemiology of complications of pregnancy and parturition, since seasonality has been postulated for multiple births (59,68), uterine bleeding (50), spontaneous abortions (43,58), preeclamptic toxemia (9,17,50,67), aplasia of one umbilical artery (51), stillbirth (58, 63) neonatal mortality (30) and other obstetrical phenomena (67). In practically all of these studies the 4-peaked curve is found as predicted by the seasonaloverripeness-hypothesis ( Fig.…”
Section: Conceptions At the Time Of The Seasonally Alternating Pattermentioning
confidence: 74%
“…Because of the accessibility of birthdates, we believe that the assessment of birthcurves of patients with all kinds of pathology is a very useful approach to elucidating the etiology and the delineation of congenital malformations and psychopathology. The same holds true for the epidemiology of complications of pregnancy and parturition, since seasonality has been postulated for multiple births (59,68), uterine bleeding (50), spontaneous abortions (43,58), preeclamptic toxemia (9,17,50,67), aplasia of one umbilical artery (51), stillbirth (58, 63) neonatal mortality (30) and other obstetrical phenomena (67). In practically all of these studies the 4-peaked curve is found as predicted by the seasonaloverripeness-hypothesis ( Fig.…”
Section: Conceptions At the Time Of The Seasonally Alternating Pattermentioning
confidence: 74%
“…A number of well-documented observations are on record which indicate that characteristic seasonal fluctuations in ovulation (50), conception (8,20,35,63,74,96), abortion (7,21,59) and birth rates (19) and in the incidence of birth defects (4,22,28,45,48,51,58,62,95) exist in virtually all populations investigated. In summarizing the available data, it was demonstrated that in the northern half of Europe ovulation and conception rates showed a major rise in the spring and a minor increase in the fall with declines in the summer and winter.…”
Section: Discussionmentioning
confidence: 99%
“…1959, 1960, 1962) that would cause the increased FSH secretion and thus by increasing the estrogen secretion would raise the protection against infection of the vaginal epithelium. Resistance against a t least puerperal infections ( Timonen et al 1965) has been found to decrease during the winter season. The frequency of this illness is significantly a t its lowest during summer and autumn.…”
Section: Discussionmentioning
confidence: 99%